2020
DOI: 10.1002/cbin.11345
|View full text |Cite
|
Sign up to set email alerts
|

YAP nuclear‐cytoplasmic translocation is regulated by mechanical signaling, protein modification, and metabolism

Abstract: Nuclear‐cytoplasmic transport is necessary for the biological function of nuclear proteins. The mechanism underlying this process is very complex and has been a subject of intense research. Yes‐associated protein (YAP), a Hippo signaling pathway effector, localizes to both the cytoplasm and the nucleus and can influence cell proliferation, stem cell status, and tissue homeostasis. Recent studies have focused on the significance of YAP distribution between the nucleus and the cytoplasm in disease, but it remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…YAP is mechanosensitive and translocates from the nucleus to the cytoplasm when cells are subjected to mechanical strain such as compression. 29,30 In fibroblasts, near +1 defects, YAP is more localized in the cell cytoplasm, suggesting the presence of mechanical strain. On the other hand, cells near À1 defects have YAP localized in nuclei.…”
Section: Forces and Dynamicsmentioning
confidence: 99%
“…YAP is mechanosensitive and translocates from the nucleus to the cytoplasm when cells are subjected to mechanical strain such as compression. 29,30 In fibroblasts, near +1 defects, YAP is more localized in the cell cytoplasm, suggesting the presence of mechanical strain. On the other hand, cells near À1 defects have YAP localized in nuclei.…”
Section: Forces and Dynamicsmentioning
confidence: 99%
“…However, the concrete mechanisms of r-ESW in vivo still need to be explored. YAP/TAZ, the effector of the Hippo pathway, has been demonstrated to play pivotal roles in mechanomeditated stem cell plasticity and stemness regulation during tissue regeneration [40,41]. Moreover, numerous studies have suggested that YAP protein activity could be regulated directly by mechanical cues from both the microenvironment, such as extracellular matrix stiffness, and other extraneous stimulation independent of the Hippo pathway [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have suggested that YAP protein activity could be regulated directly by mechanical cues from both the microenvironment, such as extracellular matrix stiffness, and other extraneous stimulation independent of the Hippo pathway [42,43]. Notably, mechanical stimuli could influence YAP nuclear-cytoplasmic distribution and in turn modulate cell biological function [40,44]. DuPont et al identified YAP/TAZ as sensors and effector proteins of mechanical cues perceived from extracellular rigidity [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we can mention at least four large groups of upstream pathways that regulate YAP nuclear localization and function [ 33 ], subdivided into: (i) mechanotransduction; (ii) polarity and tight junction proteins; (iii) the cadherin-catenin complex; and (iv) soluble growth factors.…”
Section: Extracellular and Intracellular Modulators Of Yapmentioning
confidence: 99%